Ab initio calculation of interfacial energies between transition metal carbides and fcc iron - Jung, Woo-Sang; Chung, Soon-Hyo (IOP PUBLISHING LTD, 2010)
An ab initio study was carried out on coherent and semicoherent interfacial energies for fcc Fe/MCs (NaCl structure, M = Ti, Zr, Hf, V, Nb, Ta) systems. The group V transition metal carbides have lower coherent and semicoherent interfacial energies than group IV transition metal carbides. Also, the coherent interfacial energies for fcc Fe/MCs systems are lower than those for bcc Fe/MCs systems. The difference between semicoherent and coherent interfacial energy for fcc Fe/MC systems becomes larger as the misfit increases. The semicoherent interfacial energies at relaxed interfaces Fe/TiC, Fe/ZrC, Fe/HfC, Fe/VC, Fe/NbC and Fe/TaC were 0.600 J m(-2), 0.661 J m(-2), 0.946 J m(-2),-0.050 J m(-2), 0.320 J m(-2) and 0.380 J m(-2), respectively. In order to maximize precipitation strengthening effect in austenitic steel, VC is the most favorable precipitate under consideration.
Keywords: PRECIPITATION; ENERGETICS; NITRIDES; NUCLEATION; SEQUENCE; FERRITE